Teaching Mathematics in Early Childhood Classrooms: From Beginning to End - Elmalı, Filiz; Kılıç, Melda; Aksoy, Huri Sena (Ozgen Korkmaz, 2025)
This qualitative study explores the intentional mathematics teaching practices of early childhood educators in Türkiye, focusing on the planning, implementation, and assessment phases of math instruction in preschool settings. Employing a transcendental phenomenological design, the research involved focus group discussions with twenty early childhood teachers from public schools in the eastern region of Türkiye. Data analysis revealed significant insights into how teachers conceptualize and deliver mathematics education. Findings indicate that although educators prioritized number-related concepts, they displayed limited integration of diverse mathematical domains, including measurement and data analysis and probability. Additionally, they often preferred whole-group instruction over authentic small-group or individualized approaches. Early childhood teachers also recognized the importance of developmental appropriateness, gamification, and the use of concrete materials. Furthermore, while educators utilized various attention-grabbing and participatory strategies, including storytelling, humor, and technology, the majority relied heavily on teacher-centered methods. Assessment practices were also found to be inconsistent and predominantly summative, lacking the frequency and formative depth necessary for supporting differentiated instruction. The study emphasizes the need for robust professional development, curriculum alignment, and policy interventions that support holistic, inclusive, and developmentally responsive mathematics teaching in early childhood education. Ultimately, fostering intentional, child-centered approaches to mathematics may enhance young learners’ cognitive engagement and long-term academic outcomes. © 2025, Ozgen Korkmaz. All rights reserved.
Keywords: early childhood; intentional teaching; Mathematics